Loss of Pink1 modulates synaptic mitochondrial bioenergetics in the rat striatum prior to motor symptoms: concomitant complex I respiratory defects and increased complex II‐mediated respiration. Issue 12 (21st September 2016) - Stauch, Kelly L.; Villeneuve, Lance M.; Purnell, Phillip R.; Ottemann, Brendan M.; Emanuel, Katy; Fox, Howard S.
Abstract : Purpose: Mutations in PTEN‐induced putative kinase 1 (Pink1), a mitochondrial serine/threonine kinase, cause a recessive inherited form of Parkinson's disease (PD). Pink1 deletion in rats results in a progressive PD‐like phenotype, characterized by significant motor deficits starting at 4 months of age. Despite the evidence of mitochondrial dysfunction, the pathogenic mechanism underlying disease due to Pink1‐deficiency remains obscure. Experimental design: Striatal synaptic mitochondria from 3‐month‐old Pink1‐deficient rats were characterized using bioenergetic and mass spectroscopy (MS)‐based proteomic analyses. Results: Striatal synaptic mitochondria from Pink1‐deficient rats exhibit decreased complex I‐driven respiration and increased complex II‐mediated respiration compared with wild‐type rats. MS‐based proteomics revealed 69 of the 811 quantified mitochondrial proteins were differentially expressed between Pink1‐deficient rats and controls. Down‐regulation of several electron carrier proteins, which shuttle electrons to reduce ubiquinone at complex III, in the Pink1‐knockouts suggests disruption of the linkage between fatty acid, amino acid, and choline metabolism and the mitochondrial respiratory system. Conclusions and clinical relevance: These results suggest that complex II activity is increased to compensate for loss of electron transfer mechanisms due to reduced complex I activity and loss of electron carriers within striatal nerve terminals early during disease progression. This may contribute to the pathogenesis of PD.